Grazing management and nitrogen effects on agronomic and nutritive value responses of ‘Zuri’ guineagrass under rotational stocking - Almeida, Otávio Goulart de (2022)
The Brazilian livestock farming is based on pastures as the main source of food for cattle, with tropical forage plants being the most widely used. ‘Zuri&#8217 Megathyrsus maximus (Jacq.) B.K. Simon & S.W.L. Jacobs (syn. Panicum maximum Jacq.)] was released as a new option for pasture diversification. In addition to the features of guineagrass that include high productivity and responsiveness to nitrogen fertilization, Zuri is resistant to leafhopper [Mahanarva fimbriolata; (Stål) and M. liturata (Le Peletier de Saint- Fargeau & Serville)] and leaf spot caused by the fungus Bipolaris maydis (Y. Nisik and Miyake) Shoemaker. The objectives of the present study were to explain the agronomic responses such as forage accumulation (FA), nutritive value, canopy structural characteristics, and grazing efficiency (GE) of Zuri guineagrass under rotational stocking, to pre-graze canopy heights and nitrogen fertilization rates. The experiment was carried out at USP- ESALQ in Piracicaba, Brazil, during two warm rainy seasons, using a randomized complete block design, with a 2 × 2 factorial arrangement of treatments, which corresponded to combinations of two pre-graze canopy heights [55 and 75 cm (H55 and H75, respectively)] and two N fertilization rates [150 and 300 kg N ha-1yr-1 (N150 and N300, respectively)], with four replications. The stubble height was always 50% of the pre-graze canopy height. Regardless of N rate, H75 canopies achieved 95% light interception (LI). The H55/N300 combination resulted in structural features (tiller population density, specific leaf area, and foliage angle) that made the canopy achieve 95% LI. Forage accumulation rate (FAR) and FA increased with increased canopy height (160 vs. 190 kg DM ha-1d-1 and 18370 vs. 22120 kg DM ha-1yr-1, to H55 and H75, respectively), and the GE was 8% greater for H75, 85%. In the vertical distribution of plant-part components, regardless of pre-graze height, the upper half of the canopy was composed only of leaves and the lower half with progressively decreasing leaf proportion and increasing stem and dead material down to ground level. The leaf proportion in the upper half of the canopy contributed to the lack of a height effect on nutritive value. The increase in N rate shortened the rest period of and resulted in greater FAR and FA to N150 and N300 (145 vs. 200 kg DM ha-1d-1 and 16980 vs. 23500 kg DM ha-1 yr-1, respectively), and greater GE (84%). The nutritive value was positively affected by the increase in N rate. The N300 rate resulted in greater concentrations of crude protein and in vitro digestible of organic matter, 157 and 571 g kg-1 , respectively, compared to N150. The H75 canopies were superior due to greater FAR, FA, and GE, although there was no height effect on nutritive value. Increased nitrogen fertilization favors the agronomic and nutritive value responses.